EFL Learners’ Reflection on Digitally Mediated Multimodal Project-Based Learning: Multimodal Enactment in a Listening-Speaking Class - Alvionita, Kaffah Visa; Widyaningrum, Lulut; Prayogo, Agus (Language Circle: Journal of Language and Literature, 2022)
Although teaching methods had been developed in recent years, project-based learning adopting multimodality in language teaching-learning which deals with materials development facilitating language skills and environment care at the varsity level remained underexplored yet. This qualitative content analysis study purposed to explore learners’ reflections in the enactment of multimodal project-based learning – to display how multimodal project-based learning facilitates learners’ language skills and environmental care. Twenty-four learners act as participants, do various projects, and describe their experience toward multimodal project-based learning of green listening and speaking course in the form of learners’ reflections. The findings show that students report the positive effects which influence their learning process. The results also indicate that adopting multimodal project-based learning of green listening and speaking facilitates learners’ language skills development and builds environmental awareness. Thus, the results of this research may have implications as the pioneer projects on investigating learners’ reflection of multimodal project-based learning and contribute to the development of the EFL learning process in general.